KONFLIK SEKTARIANISME DAN DOMINASI MASYARAKAT (Studi Kasus: Penolakan Pembangunan Masjid di Desa Kalikangkung, Kabupaten Tegal Tahun 2022) - Pramana, Ardine -; Sardini, Nur Hidayat -; Adnan, Muhammad - (Journal of Politic and Government Studies, 2024)
Indonesia and many other developing countries make multiculturalism both a wealth and a threat. This depends on how the government manages existing multiculturalism. Multiculturalism led to the emergence of various social groups, oneof which was a social group with a religious background. The existence of social groups causes the emergence of social conflicts in the community. Such conflicts can be sectarianism or intrareligious conflicts. This study was conducted to determine the sectarianism conflict that occurred in Kalikangkung Village, Pangkah District, Tegal Regency. Researchers analyze the chronology of conflict and the factors causing conflict. This study uses qualitative research type with case study approach. Thetypes of data used are primary and secondary data with data collection techniques through in-depth interviews. This study explains the dynamics of sectarian conflict in Kalikangkung Village. The conflict dynamics are in the form of pre-conflict, confrontation, crisis, and post-conflict stages. This study also explains the factorsthat cause conflict in the form of general factors (underlying factors) and supporting factors (participating factors). Common factors relate to the dominance of society and the influence of the Ahmadiya community. Supporting factors are actions that cause prejudice from society. In this study, researchers found the existence of social identity that creates social dominance in society. This results in social conflicts. The sectarian conflict of Kalikangkung Village is classified as a great conflict because it meets the elements of contradiction, attitude, and behavior